Calcification Induced by Type I Interferon in Human Aortic Valve Interstitial Cells Is Larger in Males and Blunted by a Janus Kinase Inhibitor. Issue 9 (September 2018) - Parra-Izquierdo, Iván; Castaños-Mollor, Irene; López, Javier; Gómez, Cristina; San Román, J. Alberto; Sánchez Crespo, Mariano; García-Rodríguez, Carmen
Abstract : Objective—: Calcific aortic valve disease is the most prevalent valvulopathy in Western countries. An unanticipated pathogenetic clue involving IFN (interferon) was disclosed by the finding of constitutive type I IFN activity associated with aortic valve calcification in children with the atypical Singleton-Merten syndrome. On this basis, the role of type I IFN on inflammation and calcification in human aortic valve interstitial cells (AVIC) was examined. Approach and Results—: IFN-α was weakly proinflammatory but potentiated lipopolysaccharide-mediated activation of NF (nuclear factor)-κB and the ensuing induction of proinflammatory molecules in human AVIC. Stimulation with IFN-α and in combination with lipopolysaccharide promoted osteoblast-like differentiation characterized by increased osteoblastic gene expression, BMP (bone morphogenetic protein)-2 secretion, and ectopic phosphatase activity. Sex differences were observed. Likewise, IFN-α treatment of human AVICs in osteogenic medium resulted in increased formation of calcific nodules. Strikingly, IFN-α–mediated calcification was significantly higher in AVICs from males, and was blocked by tofacitinib, a JAK (Janus kinase) inhibitor, and by a BMP antagonist. A female-specific protective mechanism involving the activation of PI3K-Akt (protein kinase B) pathways and cell survival was disclosed. Females exhibited higher levels of BCL2 in valve cells and tissues and lower annexin V staining on cell stimulation. Conclusions—: IFN-α acts as a proinflammatory and pro-osteogenic cytokine in AVICs, its effects being potentiated by lipopolysaccharide. Results also uncovered sex differences with lower responses in female AVICs and sex-specific mechanisms involving apoptosis. Data point to JAK/STAT (signal transducer and activator of transcription) system as a potential therapeutic target for calcific aortic valve disease. Abstract : Supplemental Digital Content is available in the text.